Колебания компрессорной лопатки при ее геометрически нелинейном деформировании - Бреславский, Иван Дмитриевич; Аврамов, Константин Витальевич (Eastern-European Journal of Enterprise Technologies, 2009)
The Shaw-Pierre nonlinear normal modes based method of nonlinear vibrations analysis of compressor blades is developed. Eigenfrequencies and eigenforms of model of a blade vibration are found. Nonlinear oscillations of a blade are analyzed, their stability are studied.